Comparative analysis of wood market between the Baltic countries, Sweden, Poland, Germany, Finland and Denmark - Hiler, Grzegorz (SLU/Southern Swedish Forest Research Centre, 2004)
The Project consists of the comparison of the wood markets in the countries around the Baltic Sea (Poland, Germany, Denmark, Sweden, Finland, Estonia, Latvia, and Lithuania). After a short introduction into the present situation on the Global market in general and the position of the biggest companies situated in forest industry a particular analysis of the markets will be done in the term of comparative confrontation. In the shadow of coming integration by the frames of EU this kind of draw up will describe position of the wood market and forestry itself and the possible changes in the free flow of the services, goods and capital in the European Community. Also special characteristics in the possibilities of the countries in transition to move into the broad market of integrated Europe will be considered in relation to its potential stock and potential productivity.